2018
DOI: 10.1002/ece3.4686
|View full text |Cite
|
Sign up to set email alerts
|

Demographic processes limit upward altitudinal range expansion in a threatened tropical palm

Abstract: Understanding the factors that determine species’ range limits is a key issue in ecology, and is fundamental for biodiversity conservation under widespread global environmental change. Elucidating how altitudinal variation affects demographic processes may provide important clues for understanding the factors limiting current and future species distributions, yet population dynamics at range limits are still poorly understood. Here, we tested the hypothesis that lower abundance at a species’ upper altitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…However, we found a strong direct positive effect of soil nutrients on plant density. Several studies showed that plant density decreases with altitude due to temperature variation and metabolic limitations at higher elevations (Angert, 2006;Souza et al, 2018). Instead of temperature gradient, for T. atacorensis, soil macronutrients variation along elevational gradient drives plant density.…”
Section: Soil Nutrients As An Important Driver Of Range Limitationmentioning
confidence: 99%
“…However, we found a strong direct positive effect of soil nutrients on plant density. Several studies showed that plant density decreases with altitude due to temperature variation and metabolic limitations at higher elevations (Angert, 2006;Souza et al, 2018). Instead of temperature gradient, for T. atacorensis, soil macronutrients variation along elevational gradient drives plant density.…”
Section: Soil Nutrients As An Important Driver Of Range Limitationmentioning
confidence: 99%
“…This pattern of variation in climatic suitability is probably linked to the physiological requirements of E. edulis for germination and growth, especially a low tolerance to dry conditions (Andrade 2001, Gatti et al 2014, which are relatively more common in Seasonal forests than in Ombrophilous forests (IBGE 1993). In addition, the low tolerance of E. edulis to low temperatures could explain the absence of this species above 1500 m altitude (Gatti et al 2008, Roberto & Habermann 2010, Souza et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…In the Brazilian Atlantic Forest, this species has a wide latitudinal distribution, from Rio Grande do Norte to Rio Grande do Sul states, and from seal level up to around 1000-1400 m a.s.l. (Henderson et al 1995, Souza et al 2018. Euterpe edulis occurs in different vegetation types within the Atlantic Forest, including Ombrophylous, Deciduous, and Restinga forests (Henderson 1995, Gatti et al 2011.…”
Section: Study Speciesmentioning
confidence: 99%
“…Since initial establishment is a critical phase of plant life (Donohue et al, 2010;Spindelböck et al, 2013), germination success in areas with the presence of adult individuals of the same species can be seen as a form of validation of the model. Therefore, it is important to highlight the mortality between seedling to adult stages (Souza, Portela, & De Mattos, 2018) were not evaluated here. So, there is a synergistic interaction between micro-and macroscale conditions that influence both initial establishment and older stages.…”
Section: Discussionmentioning
confidence: 99%